2016
DOI: 10.1111/vsu.12504
|View full text |Cite
|
Sign up to set email alerts
|

Video‐Assisted Thoracoscopic Resection of a Noninvasive Thymoma in a Cat with Myasthenia Gravis Using Low‐Pressure Carbon Dioxide Insufflation

Abstract: Low-pressure thoracic insufflation facilitated video-assisted thoracoscopic resection of cranial mediastinal masses in this cat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Common clinical presenting signs may include vomiting, regurgitation, anorexia, cough, dyspnea, tachypnea, and lethargy . Thymomas are commonly associated with paraneoplastic syndromes, including myasthenia gravis, cranial vena cava syndrome, and hypercalcemia of malignancy …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Common clinical presenting signs may include vomiting, regurgitation, anorexia, cough, dyspnea, tachypnea, and lethargy . Thymomas are commonly associated with paraneoplastic syndromes, including myasthenia gravis, cranial vena cava syndrome, and hypercalcemia of malignancy …”
Section: Introductionmentioning
confidence: 99%
“…Thymomas have been described radiographically as a soft‐tissue opacity in the ventral cranial mediastinum that may cause displacement of the heart and trachea . Megaesophagus and an alveolar infiltrate in the lung parenchyma due to aspiration pneumonia can be associated with thymomas . One study evaluating the ultrasonographic appearance of thymomas reported that thymomas are more likely to have a heterogeneous echogenicity and one or more internal cysts when compared to lymphoma, which is more uniform in echogenicity .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations